Synodality and primacy: reflections from the Australian Lutheran/Roman Catholic Dialogue - Edwards, Denis (Pacifica, 2015)
A fundamental level of Receptive Ccumenism is that of the reception by a dialoguing church of an institutional charism of a partner church as a gift of the Spirit. It is proposed here that in the Lutheran/Roman Catholic Dialogue in Australia, this kind of receptivity has been evident in two ways. First, at least in part through this dialogue, the Lutheran Church of Australia has come to a new reception of episcopacy. Second, in and through this same dialogue, Roman Catholic participants have come to see that their church has much to receive from the Lutheran Church of Australia with regard to synodality, above all in fully involving the lay faithful in synodal structures of church life.